The Nonlinear Correlation Between a Novel Metabolic Score for Insulin Resistance and Subclinical Myocardial Injury in the General Population - Wang, Zhenwei; Li, Wei; Li, Jingjie; Liu, Naifeng (Frontiers in Endocrinology, 2022)
Background: Growing studies have shown that insulin resistance (IR) is associated with cardiovascular disease (CVD), whlie the association between IR and subclinical myocardial injury (SC-MI) remains unclear. Hence we aimed to assess the association between IR and SC-MI. Methods:: In this cross-sectional study, we enrolled 6043 individuals (age: 58.43 ± 13.08 years; 46.2% men) free from CVD from the third National Health and Nutrition Examination Survey. A novel metabolic score for insulin resistance (METS-IR) was used as alternative markers of IR. Multivariate logistic regression and restricted cubic spline were performed to evaluate the associations between METS-IR and SC-MI. Results: The multivariate logistic regression analysis showed that after adjusting for cardiovascular metabolic risk factors, higher METS-IR was independently correlated with higher risk of SC-MI [as a quartile variable, Q4 vs Q1, OR (95% CI): 1.395 (1.147, 1.698), P = 0.001, P for trend < 0.001; as a continuous variable, per 10-unit increment, OR (95% CI): 1.869 (1.524, 2.292), P < 0.001]. Restricted cubic spline indicated that there was a J-curve connection between METS-IR and SC-MI. Threshold effect analysis ascertained an inflection point of 37 of METS-IR. The ORs (95% CIs) of per 10-unit increase of METS-IR for SC-MI were 0.707 (0.538, 0.928) and 1.327 (1.210, 1.456) on the left and right sides of the inflection point (P < 0.05), respectively. Subgroup analysis showed that the association between METS-IR and SC-MI was only statistically significant in participants without diabetes. Conclusions: METS-IR was nonlinearly related to SC-MI in the general population without CVD.